Achieving MSMEs business performances by innovation and value chain through competitive advantages - Utomo, Susilo; Sutrisno, Joko; Sinulingga, Gairah; Dachi, Anugerah (Linguistics and Culture Review, 2022)
Based on data from CNBC Indonesia (2019) the fashion industry has recently become a lucrative industry in Indonesia because its growth always increasing, opposite to that the product fashion made by SMEs in Indonesia is experiencing a trend of decreasing demand in its business, the number of competing products from developed countries whose prices are lower and more trendy in terms of function and appearance makes consumers prefer mass-produced products, one proof is the fashion center in the city of Bandung that been decreasing in demand for last three year, declining in public purchasing power is one of the causes of MSME products experiencing a decrease in demand, it is felt by most MSME entrepreneurs starting in 2016 until now. This is consistent with the results of research from BPS that in the year 2017 40% of the population is under pressure or crisis and ensures low purchasing power, innovation strategies, and product value are needed to be able to compete with cheap but high-quality products in the market in order to remain competitive in the market.